Desain Merdeka Belajar : Penguatan Kompetensi Pendidikan Islam Berbasis Proyek Kolaboratif Mahasiswa - mukaffan, mukaffan (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2023)
"Merdeka Belajar Program is a policy aimed at encouraging students to master competencies and knowledge that are essential and applicable as they enter the world of work. This article presents the Design Of The "Merdeka Belajar" Program for students of High School of Education, UIN Kiai Haji Achmad Siddiq Jember. The research adopts a qualitative approach with a case study design, and data is gathered through interviews, observations, and documentation. The data is then analyzed through the condensation stage, data display, and conclusion. Based on the results of the three-month implementation of the Teaching Campus program at Madrasah Aliyah Wuluhan Jember, it was found that Tarbiyah faculty students of UIN Kiai Haji Achmad Siddiq Jember were able to organize the Campus Teaching Class XI program more effectively and with better preparation, particularly concerning the administrative system for students, field supervisors, and registered schools. All parties involved at Madrasah Aliyah Wuluhan Jember, especially the teachers, showed consistency and progress in the methods, media, and adaptations introduced for an interesting and effective learning process in line with current conditions."